Figures of Speech and Imagery in The Digital Geguritan Anthology: A Stylistic Study - Husein Erwinsyah; Suwardi Endraswara; Sulis Triyono (Javanologi: International Journal of Javanese Studies, 2024)
Literary works are the manifestation of human thought. Geguritan is one of the interesting but complex literary works. Figures of speech and imagery are widely used in geguritan. This study aims to analyze figures of speech and imagery in the geguritan anthology in the GEGURITAN TEMBANG ATI Facebook group. This study uses a stylistic approach with a qualitative descriptive method. The data sources for the study were two geguritan entitled "Ibu" by J. Sumarto and "Ora bisa kasawang" by Van Ndeplok. The data collection technique used direct analysis, recording, and document analysis related to the data flow model of analysis technique. The results of the study showed that there were several figures of speech in both geguritan, namely metaphor, personification, hyperbole, simile, irony, and alliteration. The dominant figure of speech is hyperbole. In terms of imagery, the most dominant imagery was found in both geguritan, namely visual imagery, while olfactory imagery was not found in either.